Development and validation of a questionnaire to assess the perception and feedback of undergraduate medical students of Ayurveda science on teaching methods in Rachana Sharir - Sharma, Rashi; Kumar Yadav, Sunil (International Research Journal of Ayurveda & Yoga, 2025)
The present study aimed to develop and validate a comprehensive questionnaire to assess the perception and feedback of undergraduate Ayurveda students regarding teaching methods in Rachana Sharir (Human Anatomy). Questionnaires are essential tools for collecting reliable educational data; however, their accuracy depends on robust design, ethical administration, and psychometric validation. A four-stage process was employed: Item generation through literature review and expert consultation, item grouping into thematic sections, response format selection, and ethical integration. The preliminary questionnaire included six sections covering demographic details, curriculum feedback, perception and feedback on teaching methods, technological resource utilization, and overall learning experience. Content validation was performed by six subject experts in Rachana Sharir and medical education using a 4-point relevance scale. The Content Validity Index (CVI) was computed for both item level (I-CVI) and scale level (S-CVI). All items achieved I-CVI = 1.00, with S-CVI/Ave and S-CVI/UA also equal to 1.00, indicating excellent content validity. A pilot test among 1st-year BAMS students confirmed the questionnaire’s clarity, linguistic appropriateness, and contextual relevance. The final validated instrument effectively captures student perceptions across traditional and modern anatomy teaching modalities, including lectures, dissections, multimedia tools, and simulation-based learning. This validated questionnaire serves as a standardized tool for evaluating and improving anatomy pedagogy in Ayurveda institutions. It provides a reliable framework for comparative educational research and curriculum enhancement, fostering an integrative approach that bridges classical Ayurvedic knowledge with contemporary anatomical science, ultimately promoting student-centered and competency-based learning in Rachana Sharir.